SANKSI PIDANA TERHADAP PENGUSAHA YANG MEMBAYAR UPAH DI BAWAH KETENTUAN UPAH MINIMUM (STUDI KASUS PUTUSAN NOMOR 109/PID.SUS/2020/PN.CBI) - Nugraha Putra, Dhika; Asri, Ardison (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2025)
Employment development is a very important part of national development and is carried out as part of the overall development of Indonesian people and society to create a prosperous, just, and evenly distributed society, both materially and spiritually, based on Pancasila and the 1945 Constitution. Therefore, it is very interesting and important to further examine how the application of Article 81 point 66 of the Republic of Indonesia Law Number 6 of 2023 regarding the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation into Law against business actors who do not pay wages below the minimum wage provisions? And how is the application or implementation of criminal sanctions in Decision Number 109/Pid.Sus/2020/PN.Cbi related to employers who pay wages below the minimum wage provisions? To answer these issues, this legal research uses normative juridical research methods. This research uses the statutory approach, case approach, and conceptual approach. The type of data in this study is Secondary Data. The data collection technique used in this research is library research. Sources of Legal Materials include Primary Legal Materials, Secondary Legal Materials, and Tertiary Legal Materials. Data Analysis Techniques. Data analysis in this study is a qualitative analysis method. The results of the study found that the determination of the minimum wage is an important policy implemented by the government to protect workers from economic exploitation.